Using paleo-archives to safeguard biodiversity under climate change - Fordham, Damien A; Jackson, Stephen T; Brown, Stuart C; Huntley, Brian; Brook, Barry W; Dahl-Jensen, Dorthe; Gilbert, M Thomas P; Otto-Bliesner, Bette L; Svensson, Anders; Theodoridis, Spyros; Wilmshurst, Janet M; Buettel, Jessie C; et al. (Science (American Association for the Advancement of Science), 2020)
Strategies for 21st-century environmental management and conservation under global change require a strong understanding of the biological mechanisms that mediate responses to climate- and human-driven change to successfully mitigate range contractions, extinctions, and the degradation of ecosystem services. Biodiversity responses to past rapid warming events can be followed in situ and over extended periods, using cross-disciplinary approaches that provide cost-effective and scalable information for species' conservation and the maintenance of resilient ecosystems in many bioregions. Beyond the intrinsic knowledge gain such integrative research will increasingly provide the context, tools, and relevant case studies to assist in mitigating climate-driven biodiversity losses in the 21st century and beyond.